1995
DOI: 10.1002/tea.3660321007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Computer‐Assisted Supplementary Instruction for Teaching the Mole Concept

Abstract: This study examined the effect of computer-assisted instruction (CAI), used as a problem-solving supplement to classroom instruction, on students' understanding of chemical formulas and mole concept, their attitudes toward chemistry subjects, and CAI. The objective was to assess the effectiveness of CAI over recitation hours when both teaching methods were used as a supplement to the traditional chemistry instruction. We randomly selected two classes in a secondary school. Each teaching strategy was randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 35 publications
0
21
0
7
Order By: Relevance
“…Por último hay que indicar que el uso educativo de las TICs fomenta el desarrollo de actitudes favorables al aprendizaje de la ciencia y la tecnología. Como han puesto de manifiesto diversos trabajos sobre el tema (Jegede, 1991;Yalcinalp et al, 1995;Escalada y Zollman, 1997), el uso de programas interactivos y la búsqueda de información científica en Internet ayuda a fomentar la actividad de los alumnos durante el proceso educativo, favoreciendo el intercambio de ideas, la motivación y el interés de los alumnos por el aprendizaje de las ciencias. Muchos alumnos también participan en foros de debate sobre temas científicos o llegan a elaborar sus propias páginas webs y pequeños programas de simulación.…”
Section: El Papel De Las Tics En La Formación De Estudiantes De Cienciasunclassified
See 1 more Smart Citation
“…Por último hay que indicar que el uso educativo de las TICs fomenta el desarrollo de actitudes favorables al aprendizaje de la ciencia y la tecnología. Como han puesto de manifiesto diversos trabajos sobre el tema (Jegede, 1991;Yalcinalp et al, 1995;Escalada y Zollman, 1997), el uso de programas interactivos y la búsqueda de información científica en Internet ayuda a fomentar la actividad de los alumnos durante el proceso educativo, favoreciendo el intercambio de ideas, la motivación y el interés de los alumnos por el aprendizaje de las ciencias. Muchos alumnos también participan en foros de debate sobre temas científicos o llegan a elaborar sus propias páginas webs y pequeños programas de simulación.…”
Section: El Papel De Las Tics En La Formación De Estudiantes De Cienciasunclassified
“…(Gorsky & Finegold, 1992;Ehrlich et al 1993;Bedford & Fowler, 1996;Windschitl & Andre, 1998;Franco, 2000). Además de la Física, el desarrollo y aplicación de las simulaciones también desempeña, desde hace tiempo, una función educativa importante en otras materias como Biología (Jegede, 1991), Química (Yalcinalp et al, 1995) o Tecnología (Li, 1998).…”
Section: Fundamentos Y Líneas De Trabajo 11unclassified
“…Appropriate use of researchvalidated self-paced adaptive learning tools can be particularly beneficial for under-prepared students and provide a variety of students an opportunity to learn. These tools can play a central role in scaffolding student learning, helping them gain a deep understanding of the content (Yalcinalp et al, 1995;McDermott, 1996;Korkmaz and Harwood, 2004;Singh, 2008a;Kohnle et al, 2010;Marshman and Singh, 2015;Sayer et al, 2017), develop their problem-solving, reasoning, and meta-cognitive skills (Reif and Scott, 1999;Singh, 2004;Demetriadis et al, 2008;Singh and Haileselassie, 2010), and facilitate transfer of learning from one context to another .…”
mentioning
confidence: 99%
“…Morrell found no significant difference between the means of the achievement scores of the CAI group and those of the traditional group. When Yalcinalp, Geban, & Ozkan (1995) examined the effectiveness of using CAI for teaching the mole concept in high school chemistry, they found that students who used CAI accompanied with lectures scores significantly higher than did those who attended recitation hours, with respect to school subject in chemistry and attitudes towards chemistry subjects.…”
mentioning
confidence: 99%